Planning Villa Nueva - Unknown:::Creator::::::::::::
Photograph shows a group of men and women who are probably involved with the planning and building of Villa Nueva. They are sitting in a boardroom at an executive-like meeting table. There are plans on easels at the end of the table that are possibly of the Villa Nueva building. Some of the people present are: Susanne B. Wilson, front left, Mary Katherine Kelley, third person back on the left, and Joleen Callahan, 2nd person on the right.